Potential effects of omega-3 fatty acids on high density lipoprotein cholesterol and low density lipoprotein cholesterol in middle aged patients with diabetes mellitus - Habib, Tamanna Binte; Akhter, Qazi Shamima; Yeasmin, Nahid; Imam, Hasan; Chowdhury, Forhad Uddin Hasan; Hossain, Mohammad Zaid; Mirdha, Md Sohel; Islam, Md Khademul; Rabbani, Safia Binte; Alam, Md Mahbubul (Journal of Dhaka Medical College, 2020)
Background: The one of the most common metabolic disorder that remains worldwide is Diabetes mellitus. Dietary intake of omega-3 fatty acid may confer a protective effect against diabetes, improves high density lipoprotein (HDL-C) and reduce low density lipoprotein cholesterol (LDL-C) levels. Objective: To observe the effect of supplementation of omega-3 fatty acid on HDL and LDL levels in type 2 DM. Methods: A prospective interventional study was conducted from January 2017 to December 2017. A total numbers of 52 diagnosed type 2 diabetic patients of both sexes were selected with age ranging from 40 to 50 years. Among them, 27 type 2 diabetic patients with supplementation of omega 3 fatty acid (2g/day) for 12 weeks was considered as study group. Another 25 type 2 diabetic patients without supplementation of omega 3 fatty acid were considered as control group for comparison. The study subjects were selected from Outpatient Department of Endocrinology, Dhaka Medical College Hospital, Dhaka and personal contact from Dhaka city on the basis of inclusion and exclusion criteria. The research work was carried out after obtaining ethical clearance from concerned departments, Research Review Committee and Ethical Review Committee of Dhaka medical college, Dhaka. The study parameters serum HDL was estimated by enzymatic colorimetric method in auto-analyzer and serum low density lipoprotein was calculated by using Friedwald formula in Department of Laboratory Medicine, Dhaka Medical College Hospital, Dhaka. The parameters were studied 2 times in study and control groups i.e. at the beginning of study (base line) and after 12 weeks of study period. Data were collected in pre-designed structured questionnaire from the researcher by herself. For statistical analysis, Paired Student’s ‘t’ test and Unpaired Student’s ‘t’ test were performed as applicable using SPSS for windows version 16.0. Results: In this study High density lipoprotein cholesterol that is good cholesterol increased and low density lipoprotein cholesterol was decreased in diabetic patients after supplementation with omega-3 fatty acid in comparison to that of their baseline value. Again, after 12 weeks, high density lipoprotein was higher and low density lipoprotein cholesterol was lower in diabetic patients after supplementation with omega-3 fatty acid in comparison to control group. Conclusion: After analyzing the results of the study, it can be concluded that omega-3 fatty acid can improve HDL and lowers LDL levels in diabetic patients may be helpful to minimize the complications of type-2 diabetes mellitus. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 190-194